1998
DOI: 10.1089/jwh.1998.7.329
|View full text |Cite
|
Sign up to set email alerts
|

The Exploitation of Autoimmune Disease: Breast Implant Litigation and Its Dire Implications for Women's Health

Abstract: Men, women, and children are subject to a number of disease conditions that have been documented over many centuries. Among the most recently described and the least understood of these conditions are autoimmune diseases. As we unfortunately have seen in recent years, the obscure nature of autoimmune disorders has allowed scientific distortion by individuals who stand to profit by claiming a cause-and-effect relationship among some types of autoimmune conditions and a number of medical products, resulting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, autoimmune disease is not the only important safety issue for these devices. Epidemiology and immunology studies and editorial articles that have been cited in support of SGBI safety (i.e., Gabriel et al 57 , Hennekens et al 62 , Angell 63 , Connell 64 ) have devoted almost no attention to the health consequences of the local complications of pain, capsular contracture, disfigurement, chronic inflammation, rupture, silicone migration, and frequent surgical revisions. Gabriel et al acknowledged the gravity of these complications in their most recent article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, autoimmune disease is not the only important safety issue for these devices. Epidemiology and immunology studies and editorial articles that have been cited in support of SGBI safety (i.e., Gabriel et al 57 , Hennekens et al 62 , Angell 63 , Connell 64 ) have devoted almost no attention to the health consequences of the local complications of pain, capsular contracture, disfigurement, chronic inflammation, rupture, silicone migration, and frequent surgical revisions. Gabriel et al acknowledged the gravity of these complications in their most recent article.…”
Section: Discussionmentioning
confidence: 99%
“…A further example is a 1998 article on SGBIs by Connell in the Journal of Women's Health. 64 Fully 10 pages were devoted to the "dire implications for women's health" caused by litigation and junk science. The "well known complications such as capsular contracture, rupture, and bleed," also termed by Connell as "well-known local side effects of breast implants," were virtually ignored with no consideration of the rate of failure, the frequency of related local complications, their consequences, or the need for frequent additional surgeries.…”
Section: Equationmentioning
confidence: 99%
“…After several individuals with autoimmune diseases pointed a finger at the implants as an etiologic agent, the United States Food and Drug Administration (FDA) reviewed the available research and case reports and found no convincing evidence of any particular disorder related to the device. They also declared that there was evidence for implants serving a public health need [2]. Unfortunately, the publicity surrounding the issue resulted in a plethora of poor quality retrospective studies and case reports, adverse 'expert' clinical opinion, and subsequent lawsuits by the bushel.…”
mentioning
confidence: 99%